2022
DOI: 10.1097/pas.0000000000001936
|View full text |Cite
|
Sign up to set email alerts
|

The Clonal Relationship Between the Ductal and Lobular Components of Mixed Ductal-Lobular Carcinomas Suggested a Ductal Origin in Most Tumors

Abstract: The relationship between the ductal and lobular components of invasive ductolobular carcinomas (IDLC) has not been fully elucidated. In this study, the molecular alterations of both components were analyzed in a series of 20 IDLC that were selected, not only by morphologic criteria, but also by the loss of E-cadherin expression in the lobular component. We found that 80% of tumors shared alterations of driver genes in both components, being PIK3CA the most common alteration. In addition, 45% of IDLC carried CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…However, in lobular regions of MDLC-2, CDH1 promoter methylation was observed, indicating an alternative but less studied route of lobular tumor formation via epigenetic inactivation. This is an intriguing observation, suggesting that the pathogenesis of lobular regions within mDLC maybe more complex and diverse than previously thought 6,68,[78][79][80] . Our expression analysis of various previously reported 81 epithelial to mesenchymal (EMT) markers (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…However, in lobular regions of MDLC-2, CDH1 promoter methylation was observed, indicating an alternative but less studied route of lobular tumor formation via epigenetic inactivation. This is an intriguing observation, suggesting that the pathogenesis of lobular regions within mDLC maybe more complex and diverse than previously thought 6,68,[78][79][80] . Our expression analysis of various previously reported 81 epithelial to mesenchymal (EMT) markers (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Assessment of H&E and E- cadherin/p120 dual staining confirmed that each case exhibited histomorphic features in line with the latest mDLC definition i.e., admix of E-cadherin negative lobular tumor regions with at least 10-90% of E-cadherin positive ductal tumor regions (Supplementary Table S1B). Importantly, overall, these cases exhibited collision of spatially distinct ductal and lobular tumor regions 68,78 along with some regions of intermixing and hence could be broadly defined as mDLC of “collision” type. These cases were particularly amenable for downstream multi-omic profiling compared to those that exhibited more intermingling or intermixing with close proximity of histologic tumor regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations